Shifts in phenology due to global climate change: the need for a yardstick - Visser, Marcel E (The Royal Society, 2005)
Climate change has led to shifts in phenology in many species distributed widely across taxonomic groups. It is, however, unclear how we should interpret these shifts without some sort of a yardstick: a measure that will reflect how much a species should be shifting to match the change in its environment caused by climate change. Here, we assume that the shift in the phenology of a species' food abundance is, by a first approximation, an appropriate yardstick. We review the few examples that are available, ranging from birds to marine plankton. In almost all of these examples, the phenology of the focal species shifts either too little (five out of 11) or too much (three out of 11) compared to the yardstick. Thus, many species are becoming mistimed due to climate change. We urge researchers with long-term datasets on phenology to link their data with those that may serve as a yardstick, because documentation of the incidence of climate change-induced mistiming is crucial in assessing the impact of global climate change on the natural world.